2002
DOI: 10.1111/j.1745-9125.2002.tb00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Racial Profiling: Race, Class, and Personal Experience*

Abstract: Racial profiling by the police has become an increasingly controversial issue in recent years, but we know little about the extent of the problem and even less about public perceptions of profiling. This article analyzes recent national survey data on citizens' views of racial profiling. We find that both race and personal experience with profiling are strong predictors of attitudes toward profiling and that, among blacks, social class affects views of the prevalence and acceptability of the practice. The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
423
4
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(453 citation statements)
references
References 30 publications
22
423
4
4
Order By: Relevance
“…Additional concerns were raised about racial bias in pedestrian stops of citizens by police predicated on "zero-tolerance" policies to control quality-of-life crimes and policing strategies concentrated in minority communities that targeted illegal gun possession and drug trafficking (see Fagan, Zimring, and Kim 1998;Greene 1999;Skolnick and Caplovitz 2001;Fagan andDavies 2000, 2003;Fagan 2002;Gould and Mastrofski 2004). These practices prompted angry reactions among minority citizens that widened the breach between different racial/ethnic groups in their trust in the police (Lundman and Kaufman 2003;Tyler and Huo 2003;Weitzer and Tuch 2002), provoking a crisis of legitimacy with legal, moral, and political dimensions (see Wang 2001;Russell 2002;Harris 2002).…”
Section: Bias In Police Stops?mentioning
confidence: 99%
“…Additional concerns were raised about racial bias in pedestrian stops of citizens by police predicated on "zero-tolerance" policies to control quality-of-life crimes and policing strategies concentrated in minority communities that targeted illegal gun possession and drug trafficking (see Fagan, Zimring, and Kim 1998;Greene 1999;Skolnick and Caplovitz 2001;Fagan andDavies 2000, 2003;Fagan 2002;Gould and Mastrofski 2004). These practices prompted angry reactions among minority citizens that widened the breach between different racial/ethnic groups in their trust in the police (Lundman and Kaufman 2003;Tyler and Huo 2003;Weitzer and Tuch 2002), provoking a crisis of legitimacy with legal, moral, and political dimensions (see Wang 2001;Russell 2002;Harris 2002).…”
Section: Bias In Police Stops?mentioning
confidence: 99%
“…Binnen deze discussies is de gedachte dat de politie zich in haar handelen zou laten leiden door (ongefundeerde) aannames dat vooral bepaalde groepen migranten veel criminaliteit veroorzaken en om die reden dus extra aandacht behoeven. Zij zouden als gevolg hiervan bevooroordeeld optreden en daarmee, zoals het model van procedurele rechtvaardigheid helder maakt, groepen burgers van zich vervreemden, met desastreuze gevolgen voor de gepercipieerde legitimiteit van de (rechts)hand-having (Weitzer & Tuch 2002Tyler 2001Tyler , 2005Tyler , 2011. Hoewel er op basis van voornoemde perceptieonderzoeken zoals die door Amnesty in het Open Society Justice Initiative in Nederland zijn uitgevoerd wel degelijk een zorgwekkend beeld ontstaat over de wijze waarop burgers het handelen van de politie interpreteren, is actueel onderzoek wat zich echt richt op het bestuderen en analyseren van het beslisproces van politieambtenaren nog relatief schaars (Aalberts 1990;Bovenkerk 2014;Cankaya 2012;Svensson, Sollie & Saharso 2012;Van der Leun e.a.…”
Section: Discretionair Beslissen Binnen De (Rechts)handhavingunclassified
“…Studies of discrimination have focused both on attitudes and on disproportionalities in the focus police activity, showing that ethnic minorities are subject to disproportionately high levels of police attention (Brunson & Miller, 2006;Chan, 1997;Petrocelli, Piquero, & Smith, 2003;Quinton, 2013;Reiner, 2000;Weitzer & Tuch, 2002;Wortley & Owusu-Bempah, 2013). It is first and foremost young males from ethnic minorities who are subject to discrimination on the part of the police (Steffensmeier, Ulmer, & Kramer, 1998;Reitzel & Piquero, 2006).…”
Section: Previous Researchmentioning
confidence: 99%
“…One consequence of this is an increased level of distrust in the police in these areas, perhaps primarily on the part of young men from ethnic minorities (Brunson & Miller, 2006;Brunson, 2007). Research on what influences perceptions of the police has shown that the issue is a complex one, but having negative experiences of the police oneself, or hearing about others' negative experiences, have shown themselves to be important factors (Brunson, 2007;Brunson & Miller 2006;Skogan, 2012), as have perceptions of ethnic discrimination on the part of the police (Brunson & Miller, 2006;Brunson, 2007;Weitzer & Tuch, 2002) and of discrimination in society at large (Brunson & Miller, 2006;Sharp & Atherton, 2007;Weitzer & Tuch, 2002). Skogan (2012) found that negative behavior from police officers is strongly related to distrust in the police, whereas positive behavior is much less associated with a corresponding trust in or positive opinion of the police.…”
Section: Introductionmentioning
confidence: 99%